2023
DOI: 10.3390/biomedicines11071898
|View full text |Cite
|
Sign up to set email alerts
|

New Onset Autoimmune Diseases after the Sputnik Vaccine

Abstract: The vertiginous advance for identifying the genomic sequence of SARS-CoV-2 allowed the development of a vaccine including mRNA-based vaccines, inactivated viruses, protein subunits, and adenoviral vaccines such as Sputnik. This study aims to report on autoimmune disease manifestations that occurred following COVID-19 Sputnik vaccination. Patients and Methods: A retrospective study was conducted on patients with new-onset autoimmune diseases induced by a post-COVID-19 vaccine between March 2021 and December 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…2 Similarly, the vectored vaccine Sputnik has also been linked to the emergence of 28 cases of autoimmune conditions in Mexico and Argentina. 9 Alqatri et al reported that autoimmune cases were mostly linked to mRNA vaccines (Pfizer and Moderna), occurring within days to weeks after the administration of the first, second, or third doses, and were diagnosed using standard laboratory tests. 2 diabetes mellitus, and vasculitis.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…2 Similarly, the vectored vaccine Sputnik has also been linked to the emergence of 28 cases of autoimmune conditions in Mexico and Argentina. 9 Alqatri et al reported that autoimmune cases were mostly linked to mRNA vaccines (Pfizer and Moderna), occurring within days to weeks after the administration of the first, second, or third doses, and were diagnosed using standard laboratory tests. 2 diabetes mellitus, and vasculitis.…”
Section: Dear Editormentioning
confidence: 99%
“…However, there is a substantial body of evidence suggesting that both SARS-CoV-2 natural infection and COVID-19 vaccination (mRNA vaccines, vectored vaccines, and inactivated virus vaccines) are associated with the new onset or exacerbation of existing autoimmune and autoinflammatory conditions. [1][2][3][4][5][6][7][8][9] The question arises whether the current evidence is sufficient to confirm with postvaccination emergence of 31 cases of autoimmune conditions, including systemic lupus erythematosus (SLE), thyroiditis, Graves' disease, IgA vasculitis, inflammatory arthritis, dermatomyositis, ulcerative colitis, autoimmune hepatitis, autoimmune hemolytic anemia, autoimmune pancreatitis, ANCA vasculitis, myasthenia gravis, and Sjögren's syndrome (SS). 2 Similarly, the vectored vaccine Sputnik has also been linked to the emergence of 28 cases of autoimmune conditions in Mexico and Argentina.…”
Section: Dear Editormentioning
confidence: 99%
“…While it is an interesting observation, the measures of outcomes are limited by its sample size (n=12 versus n=8) and without any presented hazard ratios. However, there is a substantial body of evidence suggesting that both SARS-CoV-2 natural infection and COVID19 vaccination (mRNA vaccines, vectored-vaccines, and inactivated virus vaccines) are associated with the new onset or exacerbation of existing autoimmune and autoinflammatory conditions [1][2][3][4][5][6][7][8][9] . I would like to discuss if current evidence is enough to confirm COVID-19 and vaccination as risk factors for autoimmunity or if more evidence is needed.…”
Section: Dear Editormentioning
confidence: 99%
“…Imperatively administration of mRNA vaccines (Pfizer and Moderna) and vectored vaccines (AstraZeneca) has been linked with post-vaccination emergence of 31 cases of autoimmune conditions, including systemic lupus erythematosus (SLE), thyroiditis, Graves' disease, IgA vasculitis, inflammatory arthritis, dermatomyositis, ulcerative colitis, autoimmune hepatitis, autoimmune hemolytic anemia, autoimmune pancreatitis, ANCA vasculitis, myasthenia gravis, and Sjögren's syndrome (SS). Next, the vectored vaccine Sputnik has also been linked to the emergence of 28 cases of autoimmune conditions in Mexico and Argentina 9 .…”
Section: Dear Editormentioning
confidence: 99%